Removal of NAPL from columns by oxidation, sparging, surfactant and thermal treatment. (December 2017) - Jousse, F.; Atteia, O.; Höhener, P.; Cohen, G.
Abstract: In this paper, four treatment techniques commonly applied to Volatile Organic Compounds (VOC) removal from soil are compared in column experiments with pure sand containing a residual Light Non-Aqueous Phase Liquid (L-NAPL) contamination. Oxidation is tested through the injection of Fenton reagent, with persulfate, and combined with sparging with the injection of ozone. Surfactant treatment was conducted at low flow rates with Tween ® 80. Sparging was conducted by air injection but at a low flow rate of 1 mL min −1 . Finally several columns were thermally treated at a temperature of 80 °C. The results showed high removal (>90%) for all techniques used, although only thermal treatment on BTEX (Benzene, Toluene, Ethylbenzene and Xylenes) reached 100% efficiency. The main limiting factors of each technique were: (i) for oxidation, the solubility of the substance limited the removal; (ii) for surfactant both the solubility in the surfactant and the type of surfactant are important; (iii) for sparging, the main factors are contaminant vapor pressure and porous media grain size; (iv) for thermal treatment, the limitation arises from the contaminant vapor pressure and the medium hydraulic conductivity. A comparison with literature data shows that the results are consistent with most of the studies conducted on one technique. Highlights: Comparison of several remediation techniques at the column scale. Four techniques surfactant, oxidation, thermal, oxidant. Results are linked to contaminant properties. Results are compared to literature.